Wam based space efficient Prolog implementation in Lisp - Honorato, Mauro Jacob (2015)
This thesis proposes the implementation of a space efficient Prolog implementation based on the work of David H. D. Warren and Hassan Aït-Kaci. The Common Lisp is the framework used to the construction of the Prolog system, it was chosen both to provide a space efficient environment and a rich programming language in the sense that it supply the user with abstractions and new ways of thinking. The resulting system is a new syntax to the initial language that runs on top of the SBCL Common Lisp implementation and can abstract away or exploit the underlying system.